2022
DOI: 10.1002/glia.24241
|View full text |Cite
|
Sign up to set email alerts
|

Novel mechanism of hypoxic neuronal injury mediated by non‐excitatory amino acids and astroglial swelling

Abstract: In ischemic stroke and post-traumatic brain injury (TBI), blood-brain barrier disruption leads to leaking plasma amino acids (AA) into cerebral parenchyma. Bleeding in hemorrhagic stroke and TBI also release plasma AA. Although excitotoxic AA were extensively studied, little is known about non-excitatory AA during hypoxic injury.Hypoxia-induced synaptic depression in hippocampal slices becomes irreversible with non-excitatory AA, alongside their intracellular accumulation and increased tissue electrical resist… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 100 publications
0
2
0
Order By: Relevance
“…One of the first consequences of cerebral ischemia is the loss of synaptic transmission, which is usually reversible in the twilight zone [26]. In fact, in our laboratory, we have shown for the first time that the disappearance of synaptic transmission caused by a period of hypoxia becomes irreversible if the lack of oxygen is accompanied by the presence of certain non-excitatory amino acids [27][28][29].…”
Section: Brain Injury and Neurodegenerative Diseases: An Overviewmentioning
confidence: 91%
“…One of the first consequences of cerebral ischemia is the loss of synaptic transmission, which is usually reversible in the twilight zone [26]. In fact, in our laboratory, we have shown for the first time that the disappearance of synaptic transmission caused by a period of hypoxia becomes irreversible if the lack of oxygen is accompanied by the presence of certain non-excitatory amino acids [27][28][29].…”
Section: Brain Injury and Neurodegenerative Diseases: An Overviewmentioning
confidence: 91%
“…Focal swelling (beading) of dendrites, which resembles beads on a string, was identified by rounded regions extending beyond the initial diameter of the dendrite. The progression of dendritic beading (swelling) and fragmentation of the mitochondrial network was assessed manually by quantifying the amount of dendritic beading or mitochondrial fragmentation in an imaging field following published protocols 25, 28, 40 . Because the resolution and signal-to-noise ratio always present a challenge for analyses of small structures such as mitochondria, images were not randomized to keep track of individual mitochondria in the image sequences.…”
Section: Methodsmentioning
confidence: 99%
“…We also found that the presence of glutamine in this mixture was necessary but not sufficient (i.e., neither the application of alanine, glycine plus serine without glutamine, nor the individual application of glutamine during hypoxia induced permanent synaptic silencing). These results are remarkable given that L-glutamine is the most concentrated AA in the mixture and it is a substrate for the synthesis of glutamate and GABA [21]. Nevertheless, equimolar substitution of glutamine by histidine or threonine (a mixture of alanine, glycine and serine, plus histidine or threonine at 733 µM concentration) also produced detrimental effects of synaptic transmission [165].…”
Section: Non-excitatory Amino Acids As An Alternative Therapeutic Str...mentioning
confidence: 97%
“…In contrast, the presence of the seven-AA mixture during the hypoxia period made both the synaptic silencing [20] and the loss of membrane potential irreversible [165] (Figure 3), indicating that neurons have suffered irreversible damage. Lately, we showed that all the seven amino acids were not required to induce this detrimental effect, because with a mixture of just four AA (alanine, glutamine, glycine, and serine) the hypoxia effect was irreversible [21,165]. We also found that the presence of glutamine in this mixture was necessary but not sufficient (i.e., neither the application of alanine, glycine plus serine without glutamine, nor the individual application of glutamine during hypoxia induced permanent synaptic silencing).…”
Section: Non-excitatory Amino Acids As An Alternative Therapeutic Str...mentioning
confidence: 99%
See 1 more Smart Citation